Immunological biomarkers associated with survival in a cohort of Argentinian patients with common variable immunodeficiency - Kahn, Adrian Mario (2024)
Background: Common Variable Immunodeficiency (CVID) is the most common symptomatic syndrome among inborn errors of immunity (IEI). Although several aspects of CVID immunopathology have been elucidated, predictive factors for mortality are incompletely defined. A genetic cause can only be identified in approximately 30% of patients. Objectives: To develop a mortality predictive score based on the immunophenotypes and genotypes of CVID patients. Methods: Twenty-one patients diagnosed with CVID in Cordoba, Argentina, were analyzed for clinical and laboratory data. Immunophenotyping was done by flow cytometry. CVID-associated mutations were identified by whole exome sequencing (WES). Results: Live (15) and deceased (6) patients were compared. Univariate analysis showed significant differences in CD4+ T cells (p=0.002), Natural Killer (NK) cells (p=0.001) and memory switched B cells (p=0.001) between groups. Logistic regression analysis showed a negative correlation between CD4, NK and memory switched B cells counts and probability of survival over a 10-year period [CD4+ T cells: OR 1.01 (95% CI: 1.001- 1,020); NK cells: OR 1.07 (95% CI:1.02-1.17) and memory switched B cells: OR 26.23 (95% CI: 2.06-2651.96). ROC curve analysis identified a survival cut off point for each parameter: CD4+ T cells 546 cell/ml AUC 0.87 (sensitivity 60%-specificity 100%), memory switched B cells 0.84 cells/ml AUC 0.92 (sensitivity 100%-specificity 85%), NK cells 45 cells/ml for AUC 0.92 (sensitivity 83%-specificity 100%), %). Genetic analysis on 14 patients from the cohort (9 females, 5 males) revealed mutations associated with IEI in 6 patients. Conclusions: A score to predict mortality is proposed based on CD4, NK and memory switched B cell number in patients with CVID.